Anti-Fatigue Effect of Viola odorata L. in Forced Swimming Test in Rat - Hanieh Yadollahi; Fahimeh Safaeinejad; Homa Hajimehdipoor; Zahra Mousavi; Leila Ara; Somayeh Esmaeili (Traditional and Integrative Medicine, 2023)
Fatigue is a complex phenomenon that is explained as difficulty starting or keeping voluntary physical or mental activity leading to negative impacts on life and work performance. This study aimed to investigate the anti-fatigue effects of Viola odorata L. in an animal model. Aqueous and ethanol extracts of V. odorata were prepared and total phenolics content was determined. Then, the anti-fatigue activity of the extracts was evaluated via a weight-loaded forced swimming test in the rat. To this end, 48 male Wistar rats were randomly classified into 6 groups. The control group using distilled water and other groups with ethanol (EVO; 50, 100, 200 mg/kg) and aqueous extracts of V. odorata (WVO; 50, 100mg/kg) were gavaged once daily for four weeks. Then, the forced swimming was conducted and swimming time, as a fatigue factor was measured. In addition, to validate the effect of V. odorata on the endurance capacity of the rats, biochemical factors including glucose (Glc), lactate dehydrogenase (LDH), and tumor necrosis factor (TNF-α) were examined in the serum. Hepatotoxicity was also assessed using hematoxylin-eosin staining. Our Data indicated that the forced swimming time of the EVO-100, EVO-200, and WVO-100 groups was significantly increased. The serum Glucose in the group which received EVO-200 was increased significantly, while serum LDH levels in all treated groups were significantly decreased. Also, the serum level of TNF-α in the groups which received EVO-100 or 200 was increased significantly. However, there was no considerable difference in serum TNF-α level and no hepatotoxicity within aqueous extract groups. Pathology results showed fewer effects of the aqueous extract rather than ethanol extract on the liver. The results provide evidence for the development and use of V. odorata aqueous extract as an anti-fatigue supplement.